Kreatiewe prediking: Die noodsaak van kreatiwiteit in die preekgebeure - Johan S. Botha (Verbum et Ecclesia, 2010)
Creative preaching: The importance of creativity in the preaching process Using the limited resources for proclaiming the gospel of Jesus Christ in a rapidly changing world presents problems for preachers. Preaching in the reformed tradition is based primarily upon the Bible and the tradition of the church. Given the limitations of the age of the source, the preacher runs the risk of boring the congregation with sermons irrelevant to their living conditions, by repeating the same basic message. Preachers may run out of ideas and ways of presenting a fresh, relevant message on a weekly basis. They start employing all kinds of tricks and gimmicks in order to stay relevant. Creative preaching is suggested as an answer to this dilemma. Creative preaching is developed and described as a process in which the preacher, with the guidance of the Holy Spirit, employs creative methods like observation, association, imagination and creative thinking when creating a sermon. The sermon is structured to be creative and to stimulate the creativity of the listeners. Creative preaching could be described as stimulating preaching based on Scripture, imagination and the inspiration of the Holy Spirit.